2014
DOI: 10.3892/mmr.2014.2664
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of forkhead box O3 transcription is involved in C2-ceramide induced apoptosis and autophagy in ovarian cancer cells in vitro

Abstract: Abstract. Ceramide is a bioactive lipid which functions as a tumor suppressor, mediating processes such as apoptosis, growth arrest, senescence and differentiation. The effects of ceramide in ovarian cancers have not been well established. The objective of the present study was to investigate the effects of C2-ceramide treatment in A2780 ovarian cancer cells and its possible molecular mechanism. C2-ceramide-induced proliferation inhibition was analyzed using an MTT assay and Trypan blue test. Flow cytometry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…However, research has indicated that treatment with C2 ceramide alone cannot significantly activate autophagy after a combination therapy of chloroquine and C2 ceramide, which enhanced cell apoptosis and autophagy in lung cancer cells [50]. Importantly, previous studies applied C2 ceramide treatment at a dose of 25–50 μM to activate autophagy [51], whereas in this study, we used a dose of 15 μM to regulate PP1 (Figure 5C) activation without autophagy activation (Supplementary Figure S1). Moreover, ceramide regulated multiple downstream targets to regulate autophagy activation, cell apoptosis and phosphatase activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, research has indicated that treatment with C2 ceramide alone cannot significantly activate autophagy after a combination therapy of chloroquine and C2 ceramide, which enhanced cell apoptosis and autophagy in lung cancer cells [50]. Importantly, previous studies applied C2 ceramide treatment at a dose of 25–50 μM to activate autophagy [51], whereas in this study, we used a dose of 15 μM to regulate PP1 (Figure 5C) activation without autophagy activation (Supplementary Figure S1). Moreover, ceramide regulated multiple downstream targets to regulate autophagy activation, cell apoptosis and phosphatase activation.…”
Section: Discussionmentioning
confidence: 99%
“…Dasatinib and dihydroptychantol 2 were showed to inhibit ovarian cancer cells (SKOV3 and Hey) growth by inducing the expression of LC3B-II, Beclin1 and Atg12 [74, 75]. In A2780 ovarian cancer cells, C2-ceramide treatment benefited to cells apoptosis was through up-regulation of LC3-II [76]. MORAB-003 (farletuzumab), which is a humanized anti-folate receptor alpha (FRα) monoclonal antibody derived from optimization of the LK26 molecule, contributed to human ovarian cancer cells (A2780, HeyA8, SKOV3ip1 and IGROV1) death associated with increased expression of LC3-II and enriched autophagic vacuolization in ovarian cancer [74].…”
Section: Autophagy and Ovarian Carcinomamentioning
confidence: 99%
“…Studies extensively showed that the induction of autophagy was involved in inhibition of AKT/mTOR/ (p70S6K) signaling pathway [35, 38, 65, 74, 76, 78, 79] and activation of MAPK (ERK), JNK, and AMPK signaling pathways [36, 38, 76, 87]. Inhibition of AKT/mTOR/(p70S6K) signaling pathway and activation of MAPK (ERK), JNK and AMPK signaling pathways increased autophagy-induced cell apoptosis in ovarian cancer.…”
Section: Autophagy and Ovarian Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…Bcl-2 family positive relationship with apoptosis has been reported in references as follows: Upregulation of BCL2-associated X protein (Bax)/Bcl-2 ratio and caspase activation are involved in curcumintriggered apoptosis in SW872 human adipocytes; activation of Bcl-2 family proteins and caspases is implicated in calycosin-induced apoptosis in human ovarian cancer SKOV3 cells; and the upregulation of Bax and Fas/FasL by beta-element induces caspase-dependent apoptosis in human glioma cells in vitro [1][2][3]. Transcription positive relationship with apoptosis has been reported in references as follows: p53 transcription-dependent and p53 transcription-independent pathways play pivotal roles in manganese-induced neuronal apoptosis; upregulation of forkhead box O3 transcription is implicated in C2-ceramide-induced apoptosis in ovarian cancer cells in vitro; and epigenetic silencing of Bim transcription by Spi-1/ PU.1 facilitates apoptosis resistance in leukemia [4][5][6]. Yet low BIK outside-inside-out interactive inflammation immune-induced transcription-dependent apoptosis in normal adjacent tissues of lung adenocarcinoma is not clear.…”
Section: Introductionmentioning
confidence: 96%